Solar-aided hydrogen production methods for the integration of renewable energies into oil & gas industries. (15th July 2018) - Likkasit, Chonnawee; Maroufmashat, Azadeh; Elkamel, Ali; Ku, Hong-ming; Fowler, Michael
Graphical abstract: Highlights: The integration of renewable energies in the oil and gas industries is studied. It investigates the different methods for solar-based hydrogen production. Volumetric Receiver Reactor, Molten Salt, and electrolysers are used. Alternatives compared from the techno-economy-environ views with SMR. Abstract: This paper integrates solar energy, regarded as the most abundant renewable energy in the world, into oil and gas industries to produce the hydrogen required in crude oil upgrader processes. Three alternatives of producing hydrogen from solar energy were proposed, namely, Solar Steam Methane Reforming using a Volumetric Receiver Reactor (SSMR-VRR), Solar Steam Methane Reforming using Molten Salt (SSMR-MS), and Solar Thermal Power generation coupled with Water Electrolysis (STP-WE). Simulations of all alternatives have been done to produce 2577 kmol per hour hydrogen: that is, the demand in the crude oil upgrader process. The technical, economic, and environmental analysis is performed to compare the results of the alternatives with the conventional steam reforming of natural gas. The results suggest that SSMR-VRR has the lowest levelized cost of hydrogen production, which is 2.5 per kg of hydrogen; SSMR-MS has a highest energy efficiency of 68%, and STP-WE has the lowest greenhouse gas emissions. The economic analysis suggests that currently the thermochemical processes (SSMR-VRR and SSMR-MS) have potential for producing hydrogen required by the crude oil upgrader; however, as the renewable energy technologies progress that may lead to their capital cost decrease, solar thermal power with water electrolysis (STP-WE) will become a more promising sustainable option for hydrogen production.